Role of Na+ in the Cation Disorder of [Li1-xNax]NiO2 as a Cathode for Lithium-Ion Batteries. Issue 2 (17th January 2018) - Kim, Hanseul; Choi, Aram; Doo, Sung Wook; Lim, Jungwoo; Kim, YoungJin; Lee, Kyu Tae
Abstract : LiNiO2 is a promising cathode material for lithium ion batteries because of its high specific capacity (approximately 220 mA h g −1 ). However, there are several challenging issues in the development of LiNiO2, including its poor cycle and rate performance because of its structural deterioration due to thermodynamically unstable Ni 3+ . This paper demonstrates the role of Na + in the electrochemical performance and structural stability of [Li1-x Nax ]NiO2 (x = 0, 0.005, 0.01, 0.025, and 0.05). Charge disproportionation Ni 3+ → Ni 2+ and Ni 4+ in LiNiO2 increases the cation mixing of Li + and Ni 2+ during cycling, resulting in the poor cycle performance of LiNiO2 . However, Na + in [Li1-x Nax ]NiO2 mitigates the charge disproportionation because of the larger size of Na + than Li +, leading to the improved structural stability of [Li1-x Nax ]NiO2 . Consequently, Na + -doped LiNiO2 alleviates the increase in the cation mixing of Li + and Ni 2+ during cycling compared to bare LiNiO2 . This results in the improved cycle performance of [Li1-x Nax ]NiO2 (x = 0.05), such as approximately 76% of capacity retention after 100 cycles. Moreover, the substitution of Li + with Na + in LiNiO2 improves the storage characteristics of [Li1-x Nax ]NiO2, leading to a negligible capacity loss even after long-term storage.